Productivity and Quality of Sorghum bicolor (L.) Moench on Overburden Soil with Different Urea Applications - Syamsuddin, Syamsuddin; Furqan B, Muhammad Thoksyn; Kurniawan, Widhi; Zulkarnain, Deki (Universitas Halu Oleo, 2023)
Forage is an important factor in increasing livestock productivity, and of course, both quality and quantity are influenced by soil quality. This study aims to analyze the productivity and quality of Sorghum bicolor (L.) Moench has grown on nickel mine overburdened soil using different levels of urea. The study used a completely randomized design (CRD) consisting of 5 treatments with 4 replications with a total of 20 experimental units where the treatments used were P1 = use of urea fertilizer dose of 300 kg/ha, P2 = use of urea fertilizer dose of 400 kg/ha, P3 = use of urea fertilizer dose of 500 kg/ha, P4= use of urea fertilizer dose 600 kg/ha, and P5= use of urea fertilizer dose 600 kg/ha with the evaluated parameters (a) Sorghum bicolor (L.) Moench productivity includes dry matter production per hectare, leaf-to-stem ratio, and stem brix content, (b) chemical quality including dry matter (%), organic matter (%), crude protein (%), and crude fiber (%). The study's results showed that the application of urea fertilizer with different levels did not significantly affect the productivity and quality of Sorghum bicolor (L.) Moench has grown on nickel mining overburdened soil. Keywords: productivity, quality, Sorghum bicolor (L.) Moench, overburden, urea